2019
DOI: 10.1007/s13311-019-00764-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Therapeutics for the GAA·TTC Expansion Disease Friedreich Ataxia

Abstract: Friedreich ataxia (FRDA), the most common inherited ataxia, is caused by transcriptional silencing of the nuclear FXN gene, encoding the essential mitochondrial protein frataxin. Currently, there is no approved therapy for this fatal disorder. Gene silencing in FRDA is due to hyperexpansion of the triplet repeat sequence GAA•TTC in the first intron of the FXN gene, which results in chromatin histone modifications consistent with heterochromatin formation. Frataxin is involved in mitochondrial iron homeostasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 146 publications
(237 reference statements)
0
39
0
Order By: Relevance
“…Frataxin is a mitochondrial protein and is a component of a multiprotein complex that assembles iron-sulfur clusters. Gottesfeld reviews the molecular mechanisms of FRDA and the numerous interesting approaches to treat the disease [21]. These include excision or correction of the frataxin gene by genome engineering, gene activation with small molecules, protein replacement, and small molecules identified in cellular screens.…”
Section: Sca1mentioning
confidence: 99%
“…Frataxin is a mitochondrial protein and is a component of a multiprotein complex that assembles iron-sulfur clusters. Gottesfeld reviews the molecular mechanisms of FRDA and the numerous interesting approaches to treat the disease [21]. These include excision or correction of the frataxin gene by genome engineering, gene activation with small molecules, protein replacement, and small molecules identified in cellular screens.…”
Section: Sca1mentioning
confidence: 99%
“…Most patients are homozygous for the hyperexpansion of a guanosine-adenosine-adenosine (GAA) repeat in the first intron of the Frataxin (FXN) gene, 1 which triggers the formation of repressive chromatin inhibiting FXN messenger RNA transcription. 2 Longer repeats lead to more severe repression of frataxin expression, such that most residual FXN in patients with FRDA derives from the allele with the shorter GAA repeat (GAA1). Patients with earlier onset and more severe disease usually have longer GAA1.…”
mentioning
confidence: 99%
“…9,10 Although numerous studies point toward transcriptional initiation and/or elongation being affected by the expanded triplets, current knowledge regarding transcription control of the FXN locus in nonmutated alleles is limited. 5,[11][12][13][14][15] All studies reported thus far utilized episomal vectors containing the luciferase gene under the control of putative FXN promoter regions. 10,16 The ''strength'' of the promoter and importance of certain regions were defined relative to the luciferase expression in constructs containing nonmodified fragments of the FXN gene.…”
Section: Introductionmentioning
confidence: 99%